Predicting shear strength of SFRC slender beams without stirrups using an ANN model - Keskin, Riza S. O. (TECHNO-PRESS, 2017)
Shear failure of reinforced concrete (RC) beams is a major concern for structural engineers. It has been shown through various studies that the shear strength and ductility of RC beams can be improved by adding steel fibers to the concrete. An accurate model predicting the shear strength of steel fiber reinforced concrete (SFRC) beams will help SFRC to become widely used. An artificial neural network (ANN) model consisting of an input layer, a hidden layer of six neurons and an output layer was developed to predict the shear strength of SFRC slender beams without stirrups, where the input parameters are concrete compressive strength, tensile reinforcement ratio, shear span-to-depth ratio, effective depth, volume fraction of fibers, aspect ratio of fibers and fiber bond factor, and the output is an estimate of shear strength. It is shown that the model is superior to fourteen equations proposed by various researchers in predicting the shear strength of SFRC beams considered in this study and it is verified through a parametric study that the model has a good generalization capability.
Keywords: artificial neural network; steel fiber reinforced concrete; slender beam; shear strength; REINFORCED CONCRETE BEAMS; STEEL FIBERS; FIBROUS CONCRETE; RC BEAMS; SIZE; BEHAVIOR; FAILURE; Engineering